Managing China's energy sector: between the market and the state - Lai, Hongyi; Warner, Malcolm (Taylor & Francis, 2014)
As China has now become the largest energy consumer in the world, its energy sector has understandably huge domestic and global implications. In this Special Issue, which is an interdisciplinary one, comprising a set of eight in-depth empirical studies by leading international experts in the field, we set out to examine the management of the transformation of China's conventional and renewable energy sectors, with special attention to state–business relations and their link to the market.